Clinical experience with pamidronate in the treatment of Paget's disease of bone. Issue 12 (December 1991) - Gallacher, S J; Boyce, B F; Patel, U; Jenkins, A; Ralston, S H; Boyle, I T
Abstract : Bisphosphonates have been shown to be effective in treating the increased bone turnover associated with Paget's disease of bone. In this study two groups of patients were treated with pamidronate by intravenous infusion. In group 1 (n = 15) 30 mg of pamidronate was given once a week for six weeks. A subgroup (group 1A, n = 6) of more severely affected patients (pretreatment serum alkaline phosphatase (ALP) greater than 1000 U/l, normal range 80-280 U/l) received a further 60 mg weekly for three weeks. Group 2 (n = 24) received 45 mg of pamidronate every three months for one year. In both groups the level of ALP in serum samples decreased steadily throughout the year. In group 1 the level decreased to a mean value of 230 U/l (95% confidence interval 188-281) and in group 2 to 297 U/l (227-389). Four of the six patients in group 1A achieved normal ALP, whereas ALP remained at an increased level in all of the 10 patients in group 2 whose pretreatment ALP was greater than 1000 U/l, suggesting that a dose-response effect exists. The lowest hydroxyproline to creatinine ratios (normal ratio less than 0.033) were observed at the end of treatment in group 1, with a mean ratio of 0.022 (range 0.015-0.033) and at three months after the start of treatment in group 2 with a mean ratio of 0.029 (range 0.022-0.037). There was a significant decrease in the turnover of bone, as measured by whole body retention of radiolabelled bisphosphonate, from a mean of 49.3 to 41.0% (p less than 0.01). These data confirm that pamidronate is effective in the management of Paget's disease of bone. For patients with levels of ALP in serum samples of up to four times above the upper limit of the normal reference range, an effective and convenient regimen is 45 mg every three months for one year. For patients with higher levels of ALP higher doses may be more effective.